An Assessment of Carbon Sequestration Ecosystem Service in the Forests of Doon Valley, Western Himalaya, India. (Global Journal of Science Frontier Research, 2015)
The study focused on the carbon allocation and carbon sequestration ecosystem service provided by the forests of Doon Valley. 150 Quadrats were laid down to assess the biomass and carbon stocks and the carbon dioxide mitigation potential was estimated in each of the forest ranges (Barkot Range, Lachchiwala Range and Thano Range) of Dehra Dun Forest Division in Doon Valley, Western Himalaya, India. Carbon stock density varies from 13.39 Mg ha -1 in Scrub of Thano Range to 213.58 Mg ha -1 in Moist Deciduous Forest of Lachchiwala Range. Soil Organic Carbon Density ranged between 161.66 Mg ha -1 in Pure Pine Forest of Thano Range to 259.97 Mg ha -1 in Moist Deciduous Forest of Barkot Range. Thano Range has the carbon dioxide mitigation share of 37.29% while the Lachchiwala Range shared 35.37%. The Barkot Range contributed 27.34% of the Carbon dioxide mitigation. Various anthropogenic pressures from the villages at the forest fringes have the impact on the carbon stocks. Forests of Doon Valley have the potential to mitigate the climate change through proper and effective implementation of mitigation programmes. Reducing emissions from deforestation and forest degradation plus can be a vital programme that can be implemented to protect the forests of Doon Valley and assist in climate change mitigation.
Keywords: climate change; mitigation; carbon stocks; soil organic carbon; carbon dioxide equivalent; carbon sequestration